The Development of an Integrated Modified Free Inquiry (MFI) Biology Textbook: Preliminary Study - Masiah Masiah; Siti Rabiatul Fajri; Ramdhani Sucilestari (Postgraduate, University of Mataram, 2023)
This research is preliminary research from development research. The aim of this research is to gather information from teachers and students regarding biology learning, which includes the extent to which the inquiry model or more specifically modified free inquiry is implemented. The research method is a survey through questionnaires and interviews. The respondents involved were 711 students and 20 teachers from 14 public high schools in 3 (three) Lombok districts. Data was collected through questionnaires and interview guides and then analyzed descriptively. The results of the research showed that 2.1% of students stated that they had studied using modified free inquiry. Textbooks with attractive presentations, simple and easy-to-understand language, and detailed practical guidelines were needed. These findings will become a reference for researchers to conduct further research.